The Influence of Leadership Style, Teamwork, and Communication on the Performance of the Management of Bem Feb Utp Surakarta - Nabila Afrannida Kultsum; Dedy Rezkiyan; Zandra Dwanita Widodo (Asian Journal of Applied Business and Management, 2023)
leadership has the task of inspiring individuals to achieve organizational goals. The aim of this research is to assess how teamwork, communication and leadership style influence the performance of BEM administrators at the Faculty of Economics and Business, UTP Surakarta. This research uses quantitative methods, descriptive research design, and questionnaires and interviews as data collection methods. The research population was administrators and members of the BEM Faculty of Economics and Business, UTP Surakarta. A purposive respondent sampling strategy was used with a non-probability sampling method in the sampling process. The BEM administrators of the Faculty of Economics and Business, UTP Surakarta for the 2023–2024 academic year were used as the sample for this research. In total there are 25 people, including daily administrators, public relations, PSDM, communications and social departments. Research findings show that collaboration, communication and leadership style all have a significant influence on the performance of BEM administrators at the Faculty of Economics and Business, UTP Surakarta.